Convergent Validity of the PUTS - Brandt, Valerie Cathérine; Beck, Christian; Sajin, Valeria; Anders, Silke; Münchau, Alexander (Frontiers in Psychiatry, 2016)
Premonitory urges are a cardinal feature in Gilles de la Tourette syndrome. Severity of premonitory urges can be assessed with the “Premonitory Urge for Tic Disorders Scale” (PUTS). However, convergent validity of the measure has been difficult to assess due to the lack of other urge measures. We investigated the relationship between average real-time urge intensity assessed by an in-house developed real-time urge monitor, measuring urge intensity continuously for 5mins on a visual analogue scale, and general urge intensity assessed by the PUTS in 22 adult Tourette patients (mean age 29.8+/- 10.3; 19 male). Additionally, underlying factors of premonitory urges assessed by the PUTS were investigated in the adult sample using factor analysis and were replicated in 40 children and adolescents diagnosed with Tourette syndrome (mean age 12.05 +/- 2.83 SD, 31 male). Cronbach’s alpha for the PUTS10 was acceptable (α = .79) in the adult sample. Convergent validity between average real-time urge intensity scores (as assessed with the real-time urge monitor) and the 10-item version of the PUTS (r = .64) and the 9-item version of the PUTS (r = .66) was good. A factor analysis including the 10 items of the PUTS and average real-time urge intensity scores revealed three factors. One factor included the average real-time urge intensity score and appeared to measure urge intensity, while the other two factors can be assumed to reflect the (sensory) quality of urges and subjective control, respectively. The factor structure of the 10 PUTS items alone was replicated in a sample of children and adolescents. The results indicate that convergent validity between the PUTS and the real-time urge assessment monitor is good. Furthermore, the results suggest that the PUTS might assess more than one dimension of urges and it may be worthwhile developing different sub-scales of the PUTS assessing premonitory urges in terms of intensity and quality, as well as subjectively experienced control over tics and premonitory urges.